PENGARUH PENGGUNAAN MAM PADA IPS TERHADAP HASIL BELAJAR SISWA KELAS V SDN 41 SUNGAI RAYA - Gunawan, Bonifasius Arief; Marli, Suhardi; Kresnady, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to describe the contribution of the typemake amatch technique toward students?s learning outcomescivics learning on grade V SDN 41Sungai Raya. This research used Experiment method with (Pre-experimental design). The population of this research are allstudent of Grade V that included 20 people. Based on data analyt obtained  data analysis  an average grade 60,10 pre-test and post-test average of 71,75. The results of hypothesis testing using t-test obtained t = 4,46 and ? = 0.05% is obtained t table of 1.729, which means that (thitung> ttabel) so Ha is accepted. Thus, it can be concluded that the typemake amatch technique provides average impact on learning outcomes Civics Class V KeywordsCooperative Learning Types Make A Match, Civics LearningResult Study.